Photofuel cell comprising titanium oxide and bismuth oxychloride (BiO1−xCl1−y) photocatalysts that uses acidic water as a fuel1. Issue 16 (28th April 2015) - Fujishima, Yukiko; Okamoto, Seiji; Yoshiba, Mao; Itoi, Takaomi; Kawamura, Shogo; Yoshida, Yusuke; Ogura, Yuta; Izumi, Yasuo
<x xml:space="preserve">Abstract</x> The combination of n-type TiO2 and p-type BiOCl photooxidizing water and photoreducing the formed O2 back to water, respectively, in acidic solution enabled a sustainable photofuel cell utilizing natural light.